Outcomes after progression of disease with anti-PD-1/PDL1 therapy for advanced melanoma - Patrinely, James R. (Cancer, 2020)
BACKGROUND: Over half of patients treated with antibodies blocking programmed death-1 receptor (anti-PD-1) for melanoma experience disease progression. We aimed to identify prognostic factors and outcomes in patients with metastatic melanoma that progressed on anti-PD-1 therapy. METHODS: We evaluated 383 consecutively treated patients who received anti-PD-1 for advanced melanoma between 2009 and 2019. Patient and disease characteristics at baseline and progression, subsequent therapies, objective response rate (ORR), overall (OS), and progression free survival (PFS) were assessed. RESULTS: Of 383 patients, 247 experienced progression. The median survival after progression was 6.8 months. There was no difference in survival after progression based on primary tumor subtype, receipt of prior therapy, or therapy type. However, significantly improved survival after progression correlated with clinical features at progression, including normal LDH, more favorable metastatic stage (stage IV M1a vs. M1b/c/d), mutation status (NRAS or treatment naïve BRAF V600 vs. BRAF/NRAS wild type or treatment experienced BRAF mutant), decreasing tumor bulk, and progression at solely existing lesions. After progression, 54.3% of patients received additional systemic therapy. Patients received BRAF/MEK inhibition (n=41, ORR 58.6%, including 70.4% for BRAF/MEK naïve patients), ipilimumab (n=30, ORR 0%), and ipilimumab + nivolumab (n=11, ORR 27.3%). CONCLUSIONS: This study identified prognostic factors in advanced melanoma for patients who progressed on anti-PD-1, which includes LDH, stage, progression site, tumor size, and mutation status.